2006
DOI: 10.1128/iai.74.1.394-398.2006
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Correlates for Protection against Intranasal Challenge of Bacillus anthracis Spores Conferred by a Protective Antigen-Based Vaccine in Rabbits

Abstract: Correlates between immunological parameters and protection against) provided partial protection but failed to predict protection. Neutralizing antibody titers between 500 and 800 provided partial protection, while titers higher than 1,000 conferred protection. In conclusion, this study emphasizes that regardless of the immunization regimen or the time of challenge, neutralizing antibody titers are better predictors of protection than total anti-PA titers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 17 publications
2
61
0
Order By: Relevance
“…However, a direct correlation was found between the titers of LeTx-neutralizing antibodies and protection against challenge in rabbits (30,33,42). High titers (16,241) of toxin-neutralizing antibodies were induced by Ty21a-vectored derivatives secreting PA under control of the htrA promoter and administered i.p.…”
Section: Discussionmentioning
confidence: 99%
“…However, a direct correlation was found between the titers of LeTx-neutralizing antibodies and protection against challenge in rabbits (30,33,42). High titers (16,241) of toxin-neutralizing antibodies were induced by Ty21a-vectored derivatives secreting PA under control of the htrA promoter and administered i.p.…”
Section: Discussionmentioning
confidence: 99%
“…B. anthracis secreted proteins were obtained from different cultures of the wild-type virulent Vollum strain (pXO1 ϩ pXO2 ϩ ) and ⌬Vollum plasmid-cured (pXO1 Ϫ pXO2 Ϫ ) bacteria (145). The studies included also the B. anthracis ⌬14185 strain (27,94), a plasmid-cured derivate of the vaccine ATCC 14185 strain that is defective in proteolytic activity (42).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated the efficacy of PA in vaccines to protect against anthrax intoxication or infection [10][11][12][13]. The importance of anti-PA serum also has been shown in the identification of in vitro correlates of immunity [14][15][16][17] and in passive antibody studies [18][19][20]. This report evaluates the role of the aluminum hydroxide gel adjuvant and the excepient formaldehyde in the formulation of rPA vaccines in the rabbit model using in vitro surrogate markers (the quantitative anti-rPA IgG ELISA and toxin neutralizing antibody (TNA) assay) and efficacy studies.…”
Section: Subject Termsmentioning
confidence: 99%
“…We did not observe a decrease in the TNA assay ED 50 titers in the rabbit animal model at the highest concentration of aluminum tested (500 g). Both the anti-PA ELISA titer and toxin neutralizing antibody titers have been identified as serological correlates of immunity in rabbits and guinea pigs [13][14][15][16][17]25] and are thus important measurements in developing effective vaccine strategies. Various formulations have been tested in preparing anthrax vaccines based upon rPA for its ability to elicit optimal immunological responses.…”
Section: Effect Of Formaldehyde On Serological Response and Protectionmentioning
confidence: 99%